1991
DOI: 10.1128/iai.59.5.1853-1856.1991
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-2 and granulocyte-macrophage colony-stimulating factor stimulate growth of a virulent strain of Escherichia coli

Abstract: The effect of human recombinant interleukin-2 (IL-2) and human recombinant granulocyte-macrophage colony-stimulating factor on the growth of a virulent strain of Escherichia coli in tissue culture medium and in untreated, normal mouse serum was investigated. Both of these cytokines enhanced the growth of the microorganism two- to threefold in tissue culture medium with or without additional fetal calf serum and in untreated mouse serum. IL-4 did not have any effect on the growth of this microbe under the condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0
1

Year Published

1992
1992
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(21 citation statements)
references
References 19 publications
1
19
0
1
Order By: Relevance
“…IFN-c does not affect H. pylori growth, but binds to H. pylori First, we sought to determine the effect of IFN-g on the growth, survival and morphologic features of H. pylori. Although some cytokines can alter the growth of bacteria (Denis et al, 1991;Porat et al, 1991;Luo et al, 1993), IFN-g had no effect on the growth, survival (Supporting Information, Fig. S1) or morphologic features of H. pylori (data not shown).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…IFN-c does not affect H. pylori growth, but binds to H. pylori First, we sought to determine the effect of IFN-g on the growth, survival and morphologic features of H. pylori. Although some cytokines can alter the growth of bacteria (Denis et al, 1991;Porat et al, 1991;Luo et al, 1993), IFN-g had no effect on the growth, survival (Supporting Information, Fig. S1) or morphologic features of H. pylori (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…CagA protein is one of the most important virulent factors in H. pylori, and its expression is regulated by many environmental factors, including iron (Ernst et al, 2005), acid (Karita et al, 1996;Merrell et al, 2003;Shao et al, 2008b), sodium chloride (Loh et al, 2007;Gancz et al, 2008), bile (Shao et al, 2008a) and nitric oxide (Qu et al, 2009). Interleukin-1b (IL-1b) (Porat et al, 1991), tumor necrosis factor-a (TNF-a; Luo et al, 1993), IL-2 and granulocyte-macrophage colony-stimulating factor (Denis et al, 1991) can affect the growth and virulence properties of a virulent strain of Escherichia coli, and interferon-g (IFN-g) can upregulate the main virulence of Pseudomonas aeruginosa (Wu et al, 2005). However, no study has investigated IFN-g altering the properties of H. pylori, or more particularly, the effect on the virulence protein CagA.…”
Section: Introductionmentioning
confidence: 99%
“…Porat et al (23) have shown that virulent strains of Escherichia coli have receptors for interleukin 1 (IL-1) and that IL-1 enhances the growth of these bacteria. The growth of virulent strains of E. coli also has been shown to be enhanced by IL-2 and granulocyte-macrophage colonystimulating factor (5). Recently, Treseler et al (31) have shown that Candida albicans can bind IL-2 and that these complexes can induce the proliferation of an IL-2-dependent cell.…”
mentioning
confidence: 99%
“…В связи с этим было изучено влияние цитокинов на физиологические свойства (рост/ размножение) бактерий в условиях in vitro [21]. Оказалось, что интерлейкин IL-1, IL-2, IL-6, интерферон (INF) -γ [22], фактор некроза опухоли (TNF) -α [23] способствуют росту бактерий, за исключением IL-4 [24]. На модели культуры чумной палочки (Yersinia pestis) было показано наличие микробного рецептора, белка Caf1A (антиген сборки капсулы F1), локализованного в наружной мембране, способного связываться c IL-1 β [25].…”
unclassified